Kajian Hukum Islam Tidak Membayar Hutang pada Pinjaman Online Ilegal - Setiadi, Hari (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2022)
The law of accounts payable is permissible but it can be mandatory or vice versa, namely unlawful. Debt can make a person's way to heaven because of his intention to help others (Hablun minanna), but debt can also lead someone to hell fire if not managed properly. As is the case with illegal online loans that use loan transactions for the purpose of making profits from customers in ways that deviate from sharia provisions. For this reason, the Indonesian government emphasizes to people who are entangled in illegal online loans not to pay debt bills. This is contrary to Islamic teachings where it is obligatory to pay debts that are due. This study uses a qualitative method with a literature review approach, by finding out the terms and conditions of debt in Islam and analyzing how the law does not pay off illegal online loan debts.